Psicologia escolar e arte em uma instituição socioeducativa: possibilidades de interlocução - Teixeira, Danúbia Martins (2017)
One of the great challenges of our reality is the development of a quality education that can be reached by all people, guaranteeing them access to this social right. When dealing with young people who are in conflict with the law, this question becomes even more complex, so that it is fundamental to reflect on how institutions, services and professionals have worked with adolescents, contributing to their development. Thus, this research had as objective to reflect and analyze possibilities of intervention with adolescents in a socio-educational institution, based on the knowledge of critical School and Educational Psychology, grounded on the Historical-Cultural Theory and the use of Art as a mediator resource. Through these encounters and the contact with the Art, there was the purpose of opportunizing the elaboration of new reflections, meanings and senses, contributing to the young people thinking about their roles, activities and actions in their own life and in the other. This is characterized as an intervention research, its accomplishment was structured in fifteen meetings, in a socio-educational space located in a municipality of the state of Minas Gerais, conducted over four months with a group of young people interned. Once or twice a week we met to share aesthetic experiences, such as songs, poems, videos and photographs, which instigated dialogues on various subjects related to the study, such as work, experiences, drugs, interpersonal relationships, future planning and others. These elements supported both the bond with the adolescents and enabled the sharing of knowledge, also involving affective, cognitive, and relational issues, besides the own artistic content. After the conclusion of the meetings, we organized some axes of analysis, intending to present the institutional context, the activities developed, the difficulties and potentialities experienced in the meetings and the movement of the institution. For the analysis of the information constructed from the meetings, the themes that we considered most recurrent and significant were chosen, considering the objectives of this research and the theoretical framework used. Therefore, the axes of analysis were two: "Work in the socio-educational institution", which concerns communication, reception, possibilities, difficulties and other elements; and "The meetings and mediation of the school psychologist", in which thematic issues are discussed, such as professional mediation, the intervention activities, recurrent subjects in the conversations, perceptions about the development of the higher psychological functions of young people, their relationship with the school, and other aspects. From this study, it was possible to ponder on the concrete social condition that many adolescents who are in conflict with the law experience, the school exclusion of the young poor, practices that occur in socio-educational institutions and their relationship with marginalization and violence, inefficient and impoverished "inclusive" actions, as well as the importance of Education and Art for human development and the possible contributions of the school psychologist in these spaces and in society. There is still much to be researched, discovered, and transformed.